2001
DOI: 10.1177/147323000102900211
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Myeloblastic Leukaemia in a Patient with Bombay Blood Type: A Case Report

Abstract: A 62-year-old female was admitted to our hospital with suspected acute leukaemia and after investigation we diagnosed acute myeloblastic leukaemia (AML-M1). The patient's blood type was found to be the very rare Bombay type and surveillance of her relatives showed the same blood type in her male cousin on her mother's side. Alongside chemotherapy the patient received 4000 ml of frozen Bombay-type red cells, 1400 ml of concentrated red cells in manitol adenine phosphate solutions and 360 units of type O concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Schricker et al [10] reported successful autologous transfusions in a patient undergoing heart surgery with Bombay blood group. Okamoto et al [11] reported a patient with acute myeloblastic anaemia who was treated with chemotherapy and multiple transfusions without any adverse event. Lin-Chu and Broadberr [12] opined that the weak isoagglutinins in para-Bombay phenotype may not be very clinically significant and that when para-Bombay blood is not available, the compati- Bombay blood group has been reported to be the cause of hemolytic disease of newborn (HDN) requiring exchange transfusion [13].…”
Section: Discussionmentioning
confidence: 99%
“…Schricker et al [10] reported successful autologous transfusions in a patient undergoing heart surgery with Bombay blood group. Okamoto et al [11] reported a patient with acute myeloblastic anaemia who was treated with chemotherapy and multiple transfusions without any adverse event. Lin-Chu and Broadberr [12] opined that the weak isoagglutinins in para-Bombay phenotype may not be very clinically significant and that when para-Bombay blood is not available, the compati- Bombay blood group has been reported to be the cause of hemolytic disease of newborn (HDN) requiring exchange transfusion [13].…”
Section: Discussionmentioning
confidence: 99%